2019
DOI: 10.1111/cen.14108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucocorticoids on Thrombospondin‐1, Osteocalcin and the Thrombospondin‐1:Osteocalcin ratio in humans

Abstract: Objective: Thrombospondin-1 (TSP1), a matricellular protein, and Osteocalcin (OCN), a noncollagenous protein secreted by osteoblasts, are known to be up-and downregulated, respectively, by glucocorticoids. The aim of this study was to determine whether a ratio between TSP1:OCN was altered by changes in glucocorticoid activity in humans. Design: Prospective observational study.Setting: Tertiary university hospital in Queensland, Australia. Patients and Measurements:Patients with Cushing's syndrome (CS, n = 19),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
4
2
Order By: Relevance
“…Additional cohort studies between cats with LGAL and CE, food responsive and immunosuppressant responsive enteropathies are warranted. THBS1 is a glucocorticoid responsive protein in humans and was elevated in human patients being treated with prednisolone and with Cushing's syndrome 41,42 . In our study, no correlation was found between THBS1 abundance and cats treated with prednisolone in all groups.…”
Section: Discussioncontrasting
confidence: 74%
“…Additional cohort studies between cats with LGAL and CE, food responsive and immunosuppressant responsive enteropathies are warranted. THBS1 is a glucocorticoid responsive protein in humans and was elevated in human patients being treated with prednisolone and with Cushing's syndrome 41,42 . In our study, no correlation was found between THBS1 abundance and cats treated with prednisolone in all groups.…”
Section: Discussioncontrasting
confidence: 74%
“…These new glucocorticoid response serum protein biomarkers warrant further validation in additional clinical cohorts. While the glucocorticoid‐responsive proteins we have identified are unlikely to change in concentration solely in response to alterations in glucocorticoid activity, by combining biomarkers in a panel, the specificity is likely to increase, as we have previously shown in applying a ratio between thrombospondin‐1 and osteocalcin [6].…”
Section: Discussionmentioning
confidence: 80%
“…Both pre-and post-DEX blood samples were drawn at 1200 h to eliminate diurnal changes in concentration as a cause for any observed differences. As we previously introduced the concept of a ratio between an upand down-regulated serum proteins [6], we also investigated ratios between HMGB2 and LYZ. Encouragingly, we found that the ratio between HMGB2 and LYZ increased in 90% of participants following DEX (from 8.4 ± 0.45 to 15.7 ± 1.14, p < 0.0001), showing potential utility as a clinical indicator of DEX responsiveness.…”
Section: Validation Of Qualified Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…As for corticosteroid-induced bone loss, some prospective observational studies revealed that long-term oral corticosteroids decreased the mineralization of bone tissue ( Park et al, 2015 ). Osteocalcin was usually lowered with corticosteroid intake ( Puolijoki et al, 1992 ; Cesana‐Nigro et al, 2019 ), and biosynthesis of Collagen I was also interfered by corticosteroids ( Puolijoki et al, 1996 ). These significantly decreasing osteogenic markers also reflected the weakness of osteoblasts with corticosteroid treatment ( Brabnikova Maresova et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%